2006
DOI: 10.1177/030089160609200108
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Conventional Radiotherapy versus Accelerated Hyperfractionated Radiotherapy versus Concomitant Radiotherapy and Chemotherapy in Locoregionally Advanced Carcinoma of the Oropharynx

Abstract: The results obtained with the combination of CT and RT compared with RT alone did not reach statistical significance, but combined treatment almost doubled the five-year overall survival, relapse-free survival and locoregional control rate. Patients with advanced squamous cell carcinomas of the oropharynx who are medically suitable for the combined approach should be treated with a combination of radiotherapy and chemotherapy. The occurrence of second tumors is relatively common in these patients and may contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 73 publications
2
25
0
1
Order By: Relevance
“…Of these, 172 abstracts were excluded (review articles, non-randomised comparisons or randomised comparisons with conventionally fractionated radiotherapy), leaving a total of nine abstracts, wherein fulltext articles were retrieved wherever available for consideration for inclusion in the meta-analysis. One study (ORO 93-01) [20] published in full earlier was subsequently updated, resulting in another full-text publication [21] with mature results; appropriate data from both were included in the meta-analysis. Groupe d'Oncologie Radiotherapie Tete et Cou (GORTEC 99-02) [22] was the largest study included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 172 abstracts were excluded (review articles, non-randomised comparisons or randomised comparisons with conventionally fractionated radiotherapy), leaving a total of nine abstracts, wherein fulltext articles were retrieved wherever available for consideration for inclusion in the meta-analysis. One study (ORO 93-01) [20] published in full earlier was subsequently updated, resulting in another full-text publication [21] with mature results; appropriate data from both were included in the meta-analysis. Groupe d'Oncologie Radiotherapie Tete et Cou (GORTEC 99-02) [22] was the largest study included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…First, only two [22,25] of the five trials had sufficient patient numbers and were adequately powered for showing statistical significance. Second, two trials included oropharyngeal cancers only [21,25], whereas the other three allowed inclusion of all head and neck primary sites [22e24] except nasopharynx and paranasal sinus. Three trials used Forest plots of concurrent chemoradiotherapy (CCRT) versus altered fractionation radiotherapy (AFRT) for late xerostomia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several trials demonstrated the efficacy of concurrent chemoradiotherapy for OPSCC compared with radiation alone. These trials include the 94-01 GORTEC trial, 3 an Italian phase III trial showing improved but non-significant survival with chemoradiotherapy, 4 as well as a meta-analysis demonstrating better survival with concurrent chemoradiation versus radiation alone for HNSCC. 5 During this shift to more intense concurrent chemoradiation, advances in surgery allowed transoral resection of primary HNSCC, with better functional outcomes compared with open surgery.…”
mentioning
confidence: 99%